Associations of oxidative balance score with total abdominal fat mass and visceral adipose tissue mass percentages among young and middle-aged adults: findings from NHANES 2011–2018 - Wang, Kai; Deng, Minggang; Wu, Jinyi; Luo, Lingli; Chen, Rui; Liu, Fang; Nie, Jiaqi; Tao, Fengxi; Li, Qingwen; Luo, Xin; Xia, Fang (Frontiers in Nutrition, 2023)
The associations of oxidative balance score (OBS) with total abdominal fat mass (TAFM) and visceral adipose tissue mass (VATM) percentages have not been thoroughly examined. Therefore, we conducted this study to explore the association of OBS with TAFM and VATM percentages among young and middle-aged US adults. Young and middle-aged adults in the National Health and Nutrition Examination Survey (NHANES) from 2011 through 2018 were included. Analysis of variance and Rao-Scott adjusted chi-square tests were used to compare the characteristics across quartiles of OBS. Univariate and multivariate weighted logistic regression models were employed to explore the relationship between OBS and the risks of high TAFM or high VATM percentage in the general population and subgroups, while the interaction effects were tested with likelihood test. Weighted restricted cubic spline analyses were utilized to assess the nonlinear association of OBS with TAFM and VATM percentages. The final sample included 8734 young and middle-aged non-institutionalized U.S. adults representative for 134.7 million adults. Compared with adults in the first quartile of OBS, those with higher OBS were less likely to have high TAFM percentage, the ORs and 95% CI for adults in the second, third, and highest quartiles of OBS were 0.70 (0.53-0.94), 0.49 (0.36-0.60), and 0.25 (0.18-0.36), respectively. Similar trends were observed in the association between OBS and VATM percentage. Moreover, similar effects were confirmed in the sensitivity analyses and subgroup analyses according to demographic characteristics. Regarding OBS subclass, higher dietary OBS and lifestyle This is a provisional file, not the final typeset article OBS were also correlated with decreased ORs of high TAFM and VATM percentages. This study strongly suggests higher OBS as well as higher dietary OBS and lifestyle OBS are significantly correlated with lower risks of abdominal obesity and visceral fat accumulation. The findings highlight the importance of an antioxidant-rich diet and maintaining a healthy lifestyle in reducing the risks.